Prostorska determiniranost omrežij starejših in vloga sosedov v časovni perspektivi - Filipovič Hrast, Maša (Teorija in praksa, 2007)
In times of globalization and increasing individualisation the decreasing importance of local community is often debated. The neighbourhood is supposed to become less important as a source of social ties. At that the elderly are the group on which these trends would have the most negative impact, as they are more oriented on their immediate environment due to lower mobility. In the article we discuss what is the evaluation of elderly of their neighbourhood, the role of neighbours in their social support networks and the changes in time. At that we observe the neighbourhood as a potential actor in community care. We base our analysis on a non-representative sample of a smaller study, while putting them in the context of a larger representative study. The results indicate that the importance of neighbourhood is decreasing and that the neighbours are less often the source of various types of social support. This trend can be seen in both observed generations (middleaged and elderly). However, the difference between generations is present and indicates higher importance of neighbours for the elderly. The neighbourhood still presents (although limited) source of community care and source of ontological security.
Keywords: Družbena omrežja; Social networks; Older people; Starostniki; Soseska; Neighbourhood; Neighbourhood relations; Sosedski odnosi; sosedska pomoč